PUBLIC SERVICE RESPONSIBILITY IN THE MANAGEMENT OF ELECTRONIC POPULATION CARD (E-KTP) AND FAMILY CARD (KK) AT THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION OF BARRU DISTRICT - Jumria (P3M Stia Al Gazali Barru and Meraja media, 2021)
One form of public service is carried out by the government in the service of population administration documents including e-KTP and KK. The government must be responsible for providing population administration services that satisfy the community. However, in the provision of services carried out, there are still problems that often occur such as unsystematic, slow service, undisciplined employees, and lack of infrastructure. Therefore, the responsibility of the service provider is needed. Responsibility is proof that the organization is responsible for providing services to the community.This study aims to analyze the responsibility of public servants in managing E-KTP and KK at the Office of Population and Civil Registration of Barru Regency.This study uses a descriptive qualitative approach. The data collection used were interviews, observations, and documentation which were carried out for about 1 month.The results of the study indicate that in general the responsibility of public services in managing E-KTP and KK at the Office of Population and Civil Registration of Barru Regency is good, although there are still shortcomings that must be corrected. Based on the type of responsibility, according to Frederick Mosher, there are several shortcomings found. Including officers who still lack discipline, lack of smiles, lack of supporting facilities, sometimes long completion times, and the long-distance that the community has to travel to reach the Dukcapil office.